Personal Identity and Applied Ethics : a Historical and Philosophical Introduction. - Sauchelli, Andrea (Taylor and Francis, 2017)
"'Soul', 'self', 'substance' and 'person' are just four of the terms often used to describe the human person. Cutting across metaphysics, ethics and religion the nature of personal identity and the self is a fundamental and long-standing puzzle in philosophy. Personal Identity and Applied Ethics introduces and examines different conceptions of the self and personal identity and considers the implications of these for applied ethics. A key feature of the book is that it considers a range of different views of the self; philosophical, religious and cross-cultural, including perspectives from non-Western traditions. Within this comparative framework Andrea Sauchelli examines the following topics:Early views of the soul in Plato, Christianity and DescartesThe Buddhist 'no-self' and the self as a fiction and Hume on the selfConfucian ideas of the self and the importance of self-cultivation as constitutive of the selfLocke's theory of personal identity as continuity of consciousness and memory and objections to Locke's argument by Butler and Reid as well as contemporary criticsThe theory of 'animalism' and arguments concerning embodied concepts of personal identityNarrative theories of personal identity and moral agencyPersonal identity and self-knowledgePersonal identity and important issues in applied ethics, including abortion, euthanasia and the idea of life after deathImplications of life-extending technologies for the self and personal identity. Throughout the book Andrea Sauchelli also considers the views of important recent philosophers of personal identity such as Sidney Shoemaker, Bernard Williams, David Wiggins, Derek Parfit, Galen Strawson and Christine Korsgaard, placing these in helpful historical context. The addition of chapter summaries and annotated further reading make this a refreshing, approachable introduction to personal identity and applied ethics. It is an ideal text for courses on personal identity that consider both western and non-western approaches and that apply theories of personal identity to applied ethics. It will also be of interest to those in related subjects such as religious studies and history of ideas."--Provided by publisher.